2016
DOI: 10.3847/0004-637x/828/2/78
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray and Optical Correlation of Type I Seyfert NGC 3516 Studied With Suzaku and Japanese Ground-Based Telescopes

Abstract: From 2013 April to 2014 April, we performed X-ray and optical simultaneous monitoring of the type 1.5 Seyfert galaxy NGC3516. We employed Suzaku and five Japanese ground-based telescopes-the Pirka, Kiso Schmidt, Nayuta, MITSuME, and the Kanata telescopes. The Suzaku observations were conducted seven times with various intervals ranging from days or weeks to months, with an exposure of ∼50 ks each. The optical B-band observations not only covered those of Suzaku almost simultaneously, but also followed the sou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 112 publications
(172 reference statements)
3
56
0
Order By: Relevance
“…This is not unusual for Seyfert galaxies, as discussed by Edelson et al (2000). Recently, Noda et al (2016) found from a simultaneous X-ray and optical monitoring program during the faintest phase of NGC 3516 (2013of NGC 3516 ( -2014 that the X-ray flux and B-band variations were comparable and significantly correlated, with the B-band delayed by ∼2 days relative to the X-rays. Both results indicate that the standard X-ray reprocessing model in which the X-ray source heats a stratified accretion disk, which then reemits in the optical and ultraviolet, may not be applicable in the case of NGC 3516 and that these two emitting regions are powered primarily by different processes (Edelson et al 2000;Noda et al 2016).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…This is not unusual for Seyfert galaxies, as discussed by Edelson et al (2000). Recently, Noda et al (2016) found from a simultaneous X-ray and optical monitoring program during the faintest phase of NGC 3516 (2013of NGC 3516 ( -2014 that the X-ray flux and B-band variations were comparable and significantly correlated, with the B-band delayed by ∼2 days relative to the X-rays. Both results indicate that the standard X-ray reprocessing model in which the X-ray source heats a stratified accretion disk, which then reemits in the optical and ultraviolet, may not be applicable in the case of NGC 3516 and that these two emitting regions are powered primarily by different processes (Edelson et al 2000;Noda et al 2016).…”
Section: Introductionmentioning
confidence: 71%
“…NGC 3516 shows even more interesting properties in the high-energy band (e.g., Edelson et al 2000;Netzer et al 2002;Maoz et al 2002;Turner et al 2005;Mehdipour et al 2010;Liu et al 2014;Huerta et al 2014;Noda et al 2016). Edelson et al (2000) showed that there are uncorrelated trends on longer timescales between the X-ray and optical bands, which was supported with the later findings of Maoz et al (2002).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…In addition to the AGN STORM campaign, a series of studies on other AGN have come to similar conclusions -e.g. NGC 2617 (Shappee et al 2014), NGC 6814 (Troyer et al 2016), NGC 3516 (Noda et al 2016) and Fairall 9 (Pal et al 2017). In addition, Buisson et al (2017) analyzed a sample of 21 AGN with Swift and find that the UV lags generally appear to be longer than expected for a thin disc (also see Jiang et al 2017).…”
Section: Bandsmentioning
confidence: 99%
“…This is the equivalent to the disks being too big (the lag too large) by a factor of 1.6 based on the observed flux compared to the accretion disk model. More recently, observations of NGC2617 (Shappee et al 2014), NGC3516 (Noda et al 2016), NGC6814 (Troyer et al 2016), Fairall9 (Pal et al 2017), Ark120 (Gliozzi et al 2017), and a sample of 21 AGNs in the Swift archive (Buisson et al 2017) all find lags that are longer than expected for a standard thin disk. Both Pan-STARRS and the Dark Energy Survey (DES) are obtaining light curves of quasars in multiple photometric bands, allowing for determination of the average sizes from a large number of objects (Jiang et al 2017;Mudd et al 2017).…”
Section: Introductionmentioning
confidence: 97%